Peran Pengetahuan dan Pemberdayaan Ibu Hamil dalam Deteksi Dini Risiko Kehamilan: Tinjauan Literatur - Nina Surya Fitri Yanti; Gunavathy Selvarajh; Herma Yesti; Lili Fitriati Rahmah (Maternity and Neonatal : Jurnal Kebidanan, 2026)
This study aims to analyze the role of maternal knowledge and empowerment in the early detection of pregnancy risks through a literature review. Early detection of pregnancy-related risks is essential to prevent maternal and neonatal complications. In addition to antenatal care services, individual factors such as maternal knowledge and empowerment play an important role in improving the ability to recognize danger signs during pregnancy. This study employed a literature review method by searching articles from Google Scholar, PubMed, and ScienceDirect within the period of 2015–2025. The findings indicate that maternal knowledge is associated with the ability to identify pregnancy danger signs, while empowerment contributes to health-related decision-making. Family and community support further strengthen the implementation of health behaviors. It can be concluded that improving maternal knowledge and empowerment is a key strategy in optimizing the early detection of pregnancy risks